Physician Beware: Severe Cyanide Toxicity from Amygdalin Tablets Ingestion. (24th August 2017) - Dang, Tam; Nguyen, Cham; Tran, Phu N.
Abstract : Despite the risk of cyanide toxicity and lack of efficacy, amygdalin is still used as alternative cancer treatment. Due to the highly lethal nature of cyanide toxicity, many patients die before getting medical care. Herein, we describe the case of a 73-year-old female with metastatic pancreatic cancer who developed cyanide toxicity from taking amygdalin. Detailed history and physical examination prompted rapid clinical recognition and treatment with hydroxocobalamin, leading to resolution of her cyanide toxicity. Rapid clinical diagnosis and treatment of cyanide toxicity can rapidly improve patients' clinical outcome and survival. Inquiries for any forms of ingestion should be attempted in patients with clinical signs and symptoms suggestive of poisoning.